Upaya Pengentasan Kemiskinan di Indonesia Melalui Pemberdayaan Zakat dalam Perspektif Ekonomi Syariah - Salsabila, Balqis; Tsal-Tsabila, Nadia; Isnaeni, Devi (Islamic Economics and Business Review, 2024)
Abstract Poverty is still a complex and difficult problem in various countries around the world. Likewise in Indonesia, the existing poverty rate as of March 2023 reached 25.90 million people or equivalent to 9.36% of the Indonesian population. As a country with a majority Muslim population, zakat can be an instrument that has great potential in overcoming poverty in Indonesia. The more zakat is collected and distributed appropriately, then zakat can be a good solution in alleviating poverty. For this reason, this research was prepared with the aim of discussing various efforts to alleviate poverty in Indonesia through zakat empowerment in sharia economic review. This research in its arrangement uses a qualitative descriptive method with a literature study approach. The data used in this research is secondary data obtained from relevant research that has been conducted by previous researchers. The result of this research is that efforts to alleviate poverty in Indonesia through zakat have been successfully carried out by the BAZNAS RI institution by distributing zakat to mustahik so that it contributes 1.76% to national poverty alleviation in September 2022 or the equivalent of helping 26.36 million people. Keywords: Poverty, Sharia Economics, Zakat   Abstrak Kemiskinan masih menjadi persoalan yang kompleks dan menyulitkan di berbagai negara di seluruh dunia. Begitupun di Indonesia, angka kemiskinan yang ada per Maret 2023 mencapai 25,90 juta jiwa atau setara dengan 9,36% penduduk Indonesia. Sebagai negara dengan penduduk mayoritas pemeluk agama Islam, zakat dapat menjadi instrumen yang berpotensi besar dalam mengatasi kemiskinan di Indonesia. Semakin banyak zakat yang terkumpul dan didistribusikan dengan tepat, maka zakat dapat menjadi sebuah solusi yang baik dalam pengentasan kemiskinan. Untuk itu, penelitian ini disusun dengan tujuan untuk membahas berbagai upaya pengentasan kemiskinan di Indonesia melalui pemberdayaan zakat dalam tinjauan ekonomi syariah. Penelitian ini dalam susunannya menggunakan metode deskriptif kualitatif dengan pendekatan studi kepustakaan. Data yang digunakan dalam penelitian ini adalah data sekunder yang diperoleh dari penelitian yang relevan yang telah dilakukan oleh peneliti sebelumnya. Hasil dari penelitian ini adalah upaya pengentasan kemiskinan di Indonesia melalui zakat berhasil dilakukan oleh lembaga BAZNAS RI dengan menyalurkan zakat kepada mustahik sehingga memberikan kontribusi sebesar 1,76% terhadap pengentasan kemiskinan nasional pada September 2022 atau setara dengan membantu 26,36 juta jiwa. Kata kunci: Ekonomi Syariah, Kemiskinan, Zakat